2016
DOI: 10.18632/oncotarget.12531
|View full text |Cite
|
Sign up to set email alerts
|

Selenite promotes all-trans retinoic acid-induced maturation of acute promyelocytic leukemia cells

Abstract: Selective targeting of the PML/RARα oncoprotein demonstrates a successful molecular targeted therapy in acute promyelocytic leukemia (APL) with a typical t(15:17) chromosomal translocation. The zinc-thiolate coordination is critical for structural stability of zinc finger proteins, including the PML moiety of PML/RARα. Based on the known interaction of redox-active selenium compounds with thiolate ligands of zinc, we herein have investigated the abrogatory effects of selenite alone or in combination with all-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…PMA was added at a final concentration of 200 ng/ml to the cells (3x10 5 cells/well). Immediately, 10 µl of CCK-8 was added to each well, with each experimental group paired with three parallel control groups, and the cells were incubated for 1 h (37˚C, 5% CO 2 ) prior to measuring the absorbance at 412 nm (31).…”
Section: Methodsmentioning
confidence: 99%
“…PMA was added at a final concentration of 200 ng/ml to the cells (3x10 5 cells/well). Immediately, 10 µl of CCK-8 was added to each well, with each experimental group paired with three parallel control groups, and the cells were incubated for 1 h (37˚C, 5% CO 2 ) prior to measuring the absorbance at 412 nm (31).…”
Section: Methodsmentioning
confidence: 99%
“…An early clinical study reported a decrease in total leukocyte counts, immature leukocytes, and spleen size upon oral administration of selenium cystine (diseleno - dialanine) in patients with both CML and AML (Weisberger & Suhrland, 1956). Since then several in vitro studies have demonstrated the anti-leukemic properties of sodium selenite in leukemia cell lines (Jiang Xr, 1992; Liao, Bian, Xie & Peng, 2017; Misra et al, 2016). Sodium selenite supplementation was effective in decreasing circulating leukemia cells in murine Friend erythroleukemia (FV) as well as murine CML models (Gandhi et al, 2014).…”
Section: Selenium-dependent Effects On Cancer Stem Cells In Leukemiamentioning
confidence: 99%
“…4 This protein has been considered to have a critical role in APL pathogenesis, while blocking apoptosis and maturation of promyelocytes. 5 Although it has been mostly confirmed that all-trans retinoic acid (ATRA) induces complete remission in near 90% of APL patients, about half of the patients treated with ATRA may develop the ATRA-related syndrome. 2,6 So, there is still intense interest in new chemicals and strategies with therapeutic potential for APL.…”
Section: Introductionmentioning
confidence: 99%